Newly Explored Faecalibacterium Diversity Is Connected to Age, Lifestyle, Geography, and Disease - De Filippis, Francesca; Pasolli, Edoardo; Ercolini, Danilo (Current biology, 2020)
Faecalibacterium is prevalent in the human gut and a promising microbe for the development of next-generation probiotics (NGPs) or biotherapeutics. Analyzing reference Faecalibacterium genomes and almost 3,000 Faecalibacterium-like metagenome-assembled genomes (MAGs) reconstructed from 7,907 human and 203 non-human primate gut metagenomes, we identified the presence of 22 different Faecalibacterium-like species-level genome bins (SGBs), some further divided in different strains according to the subject geographical origin. Twelve SGBs are globally spread in the human gut and show different genomic potential in the utilization of complex polysaccharides, suggesting that higher SGB diversity may be related with increased utilization of plant-based foods. Moreover, up to 11 different species may co-occur in the same subject, with lower diversity in Western populations, as well as intestinal inflammatory states and obesity. The newly explored Faecalibacterium diversity will be able to support the choice of strains suitable as NGPs, guided by the consideration of the differences existing in their functional potential. [Display omitted] •Faecalibacterium species and strain diversity in human and animal gut were explored•Twenty-two new Faecalibacterium-like species were identified•Faecalibacterium diversity varies according to age, origin, lifestyle, and disease•Faecalibacterium species show distinct functional potential Faecalibacterium is one of the most promising taxa for the development of novel probiotics. De Filippis et al. explore Faecalibacterium diversity in human and animal guts, highlighting the presence of 22 novel species with different functional potential and diverse associations with diet, health, and disease.